Osteoporosis Treatment with Anti-Sclerostin Antibodies—Mechanisms of Action and Clinical Application - Rauner, Martina (J Clin Med, 2021)
Osteoporosis is characterized by reduced bone mass and disruption of bone architecture, resulting in increased risk of fragility fractures and significant long-term disability. Although both anti-resorptive treatments and osteoanabolic drugs, such as parathyroid hormone analogues, are effective in fracture prevention, limitations exist due to lack of compliance or contraindications to these drugs. Thus, there is a need for novel potent therapies, especially for patients at high fracture risk. Romosozumab is a monoclonal antibody against sclerostin with a dual mode of action. It enhances bone formation and simultaneously suppresses bone resorption, resulting in a large anabolic window. In this opinion-based narrative review, we highlight the role of sclerostin as a critical regulator of bone mass and present human diseases of sclerostin deficiency as well as preclinical models of genetically modified sclerostin expression, which led to the development of anti-sclerostin antibodies. We review clinical studies of romosozumab in terms of bone mass accrual and anti-fracture activity in the setting of postmenopausal and male osteoporosis, present sequential treatment regimens, and discuss its safety profile and possible limitations in its use. Moreover, an outlook comprising future translational applications of anti-sclerostin antibodies in diseases other than osteoporosis is given, highlighting the clinical significance and future scopes of Wnt signaling in these settings.